2014
DOI: 10.1016/j.jcs.2014.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of zein dough characteristics using dilute organic acids

Abstract: Abbreviations: T g , glass transition temperature; SDS-PAGE, sodium dodecyl sulphatepolyacrylamide gel electrophoresis; FTIR, fourier transform infrared spectroscopy; CLSM, confocal laser scanning microscopy. 2 HIGHLIGHTSLactic and acetic acids increase zein dough extensibility but maintain cohesiveness Fine and uniform zein dough fibril structure is formed with acid preparation Zein-starch doughs prepared with acids can hold air and be inflated by AlveographyZein dough improvement apparently due to change in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
41
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 19 publications
8
41
0
Order By: Relevance
“…The author concluded that the visco-elasticity of zein was governed by its T g and that fibre formation was apparently responsible for the visco-elasticity of the zein-starch doughs. Such zein-starch doughs can also expand and hold gas (Sly et al, 2014;Berta et al, 2015). Dough viscosity has been found to be the major factor affecting gas bubble structure formation (Berta et al, 2015).…”
Section: Dough Formationmentioning
confidence: 99%
See 2 more Smart Citations
“…The author concluded that the visco-elasticity of zein was governed by its T g and that fibre formation was apparently responsible for the visco-elasticity of the zein-starch doughs. Such zein-starch doughs can also expand and hold gas (Sly et al, 2014;Berta et al, 2015). Dough viscosity has been found to be the major factor affecting gas bubble structure formation (Berta et al, 2015).…”
Section: Dough Formationmentioning
confidence: 99%
“…3). Several researchers have observed fibrils in zein doughs by SEM and confocal laser scanning microscopy (CLSM) and suggested that fibril formation is a critical step in zein visco-elastic dough formation (Lawton, 1992;Schober et al, 2010;Sly et al, 2014).…”
Section: Influence Of Secondary Structure On Dough Functionalitymentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the dough making properties of zein, the maize prolamin, can be considered because commercial zein (predominantly α-zein) forms a viscoelastic dough when hydrated above the glass transition temperature (T g ) of zein in water (~28ºC) (Lawton, 1992) and when mixed with starch or gluten-free flour can expand a bubble by Alveography (Sly et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Although maize does not contain gluten, gluten-like functionality of zein (maize prolamin) dough as a result of acidification with lactic acid and acetic acid has been reported (Sly et al, 2014). The lactic acid bacteria fermentation process also acts on the other major structural component in dough, namely starch (Petrofsky and Hoseney, 1995).…”
Section: Introductionmentioning
confidence: 99%